2022
DOI: 10.1038/s41379-022-01113-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity in DNA methylation and chromosomal alterations in diffuse gliomas and meningiomas

Abstract: Adult-type diffuse gliomas and meningiomas are the most common primary intracranial tumors of the central nervous system. DNA methylation profiling is a novel diagnostic technique increasingly used also in the clinic. Although molecular heterogeneity is well described in these tumors, DNA methylation heterogeneity is less studied. We therefore investigated the intratumor genetic and epigenetic heterogeneity in diffuse gliomas and meningiomas, with focus on potential clinical implications. We further investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…In the relapse setting in medulloblastoma, there has however been reports of methylation subclass switches in rare cases [ 20 ], but no details on the methylation alterations. Within adult brain tumours, we previously found spatial intratumour heterogeneity of methylation subclasses in GBM [ 44 ] (according to classifier v11b2 and 11b4) and high-grade meningioma, but not in LGG (v12.5) [ 8 ]. The subclasses in the paediatric brain tumours examined here were however stable for all spatial and temporal patients (classification score ≥ 0.9; MNP classifier v12.5), which is promising for clinical diagnostics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the relapse setting in medulloblastoma, there has however been reports of methylation subclass switches in rare cases [ 20 ], but no details on the methylation alterations. Within adult brain tumours, we previously found spatial intratumour heterogeneity of methylation subclasses in GBM [ 44 ] (according to classifier v11b2 and 11b4) and high-grade meningioma, but not in LGG (v12.5) [ 8 ]. The subclasses in the paediatric brain tumours examined here were however stable for all spatial and temporal patients (classification score ≥ 0.9; MNP classifier v12.5), which is promising for clinical diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the LGG had on average one more biopsy per patient for this analysis, which increases their number of DMPs meaning that differences between the tumour types probably is even larger than the numbers suggest. We have previously reported an average of 21,000 DMPs in adult GBM (grade 4 tumour), 24,000 in adult high-grade meningioma, 17,000 in adult LGG and only 100 in adult low-grade (grade 1) meningioma [ 8 , 44 ]. The pattern of more alterations with increasing tumour grade was also observed here for the paired primary and relapse paediatric patients, where the aggressive and fast-growing AT/RT and HGG had significantly more DMPs than the LGGs etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been demonstrated that DNA methylation can result in the molecular and phenotypic heterogeneity of primary ADCs and lymph node metastases [ 28 ]. Obviously, it has been reported that global DNA methylation can reflect spatial heterogeneity [ 29 ]. Similarly, the DNA methylation shows extensive heterogeneity in time and space in glioblastoma [ 30 ].…”
Section: Abnormal Dna Methylation In Cancermentioning
confidence: 99%
“…Several studies have sampled specimen from different regions of the same glioblastoma tumour and profiled them using methylation-based classification [ 87 , 88 , 89 , 90 ]. We showed that 5 of 12 (42%) glioblastoma tumours had different methylation subclasses within their tumours [ 87 ].…”
Section: Heterogeneity In Diffuse Gliomasmentioning
confidence: 99%